Update on IJTLD OPEN: the future is open - H.D. Blackbourn; G.B. Migliori (IJTLD Open)
The launch of IJTLD OPEN, which is fully compliant with Plan S, has extended our author base and allowed readers worldwide to access the content for free. PubMed Central (PMC) has recently approved the journal for indexing (including indexing by PubMed), which will further improve visibility and access. Because authors retain copyright they can use their articles without restriction (e.g., to post on free digital repositories), helping to further disseminate their research. All these factors help to ensure that IJTLD OPEN has maximum reach and impact. However, we recognise that fees for open access may present a barrier for authors based in low- to middle-income countries. We call on the international community to ensure funding support for open access is broadly available, with equal opportunity for researchers worldwide.